(untitled) (Research, Society and Development, 2024)
The aim of the present study was to compare the Protaper Universal® nickel-titanium rotary endodontic files with the ProFile Vortex® nickel-titanium rotary files, evaluating the cutting capacity of the instruments. To analyze the cutting capacity, one hundred phenolic resin blocks containing simulated channels with 75° of curvature were weighed on a digital analytical scale, obtaining the initial weights (P0) and after instrumenting the channels, these blocks were again weighed, obtaining the final weights (P1). Forty instruments were divided into two groups. Group A: twenty ProFile Vortex® n°25 instruments; 25mm; taper.06 and Group B: twenty ProTaper® F1 instruments; 25mm. It was subdivided into two subgroups with ten samples each, according to the number of uses, being established as follows: groups A0 and B0, instruments with no use and groups A5 and B5, instruments with five uses. Descriptive statistics, the Student “t” test and the Mann-Whitney test were performed. In all blocks there was weight loss, but without statistical significance (pvalue>0.05). The Profile Vortex® instruments removed more material with statistical significance (pvalue>0.05) when compared to the Protaper® instruments. The authors concluded that the cutting capacity depending on the number of uses in the parameters used in this study were greater for the Profile Vortex® instruments when compared to the Protaper® instruments.